1984
DOI: 10.1007/bf00272999
|View full text |Cite
|
Sign up to set email alerts
|

Harvey-ras allele deletion detected by in situ hybridization to Wilms' tumor chromosomes

Abstract: We have examined the chromosomes from a case of sporadic Wilms' tumor using in situ hybridization to determine whether the Ha-ras (c-Ha-ras 1) oncogene had been deleted as the result of a reciprocal chromosomal translocation between the short arm of chromosome 11 (breakpoint 11p13) and the long arm of chromosome 12 (breakpoint 12q13). Neither the derivative 11 nor derivative 12 chromosome hybridized significantly to the Ha-ras probe, which indicated that this cellular oncogene was deleted as a consequence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Chromosomal deletions of lip have been observed in neoplastic cells from some Wilms tumor patients (28,29). In most such tumors that were examined, c-rasH has been shown to be located outside the deleted segment (30,31); however, it was within the deleted segment in a few of them (32). The data are, thus, generally analogous to those that we have obtained, namely that c-src is outside of the region of the deletion.…”
Section: Discussionsupporting
confidence: 71%
“…Chromosomal deletions of lip have been observed in neoplastic cells from some Wilms tumor patients (28,29). In most such tumors that were examined, c-rasH has been shown to be located outside the deleted segment (30,31); however, it was within the deleted segment in a few of them (32). The data are, thus, generally analogous to those that we have obtained, namely that c-src is outside of the region of the deletion.…”
Section: Discussionsupporting
confidence: 71%
“…According to this model, sporadic tumours develop following two independent events occurring in both copies of the same gene, while hereditary cases involve germline transmission of one altered gene and acquisition of a somatic mutation on the other allele. Although several studies in the 1980s reported WT1 ‐affected WTs behaving in similar manner to retinoblastoma [], subsequently the ‘two‐hit’ model for WT has not been as strongly supported as it has been for retinoblastoma , perhaps due to genetic heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that somatic changes, either rearrangements, point mutations, or deletions to the c-Ha-ras-1 oncogene, have been correlated to increased incidences of the tumour. This oncogene is localized at 1 lp14 immediately distal to the 1 lp13 segment and could be affected by a deletion in this area (Eccles et al, 1984). Other studies, however, have suggested that there must be another locus involved in the formation of Wilms tumour since no deletion of the oncogene was detected where AWTA was diagnosed (Huerre et al, 1983).…”
Section: Discussionmentioning
confidence: 97%